Conversion study of hepatocellular carcinoma using HAIC combined with lenvatinib and PD-1/L1 immunotherapy under the guidance of BCLC staging - Zhang, Weihao; Zhao, Xiaohui; Gao, Wei; Si, Tongguo; Zou, Qiang; Yang, Xueling; Xing, Wenge; Yu, Haipeng (Frontiers in Immunology, 2025)
ObjectiveThis study aimed to assess the efficacy and safety of hepatic arterial infusion chemotherapy (HAIC) combined with lenvatinib and immunotherapy and explore its potential as a conversion treatment for unresectable hepatocellular carcinoma (uHCC).MethodsA retrospective analysis was performed on clinical data from patients with uHCC who underwent HAIC, lenvatinib, and PD-1/PD-L1 immunotherapy. Data were collected from our hospital between November 2018 and December 2022. Efficacy was assessed based on the modified Response Evaluation Criteria in Solid Tumors (mRECIST). The primary endpoints were overall survival (OS), progression-free survival (PFS), and conversion therapy rate. Additionally, survival status curves were plotted using the Kaplan-Meier method. Lastly, prognostic risk factors affecting conversion therapy and survival outcomes were evaluated using Logistic and Cox regression models.ResultsAs of December 2022, 318 patients were included, comprising 40 patients (12.6%) in BCLC stage A, 123 patients (38.7%) in BCLC stage B, and 155 patients (48.7%) in BCLC stage C. The overall objective response rate (ORR) was 47.1%, whilst the disease control rate (DCR) was 85.5%. Meanwhile, the median overall survival (mOS) for the entire cohort was 21.7 months (95% CI: 19.7-24.3), with a median progression-free survival (mPFS) of 11.4 months (95% CI: 9.4-13.4). A total of 110 patients (34.6%) underwent conversion surgery. Multivariate logistic regression analysis identified BCLC stage as the sole independent risk factor affecting eligibility for conversion therapy. Subgroup analysis revealed that BCLC-B stage patients who achieved successful conversion therapy demonstrated significantly superior outcomes compared to those who did not undergo successful conversion therapy (median OS: 29.3 months [95% CI: 24.3-NA] vs. 19.7 months [95% CI: 17.2-24.6], P = 0.0013). Multivariate regression analysis identified the BCLC stage, the presence of distant metastasis, and receipt of conversion therapy as independent prognostic factors influencing OS. Among the cohort, 169 (53.1%) experienced grade 3-4 adverse events (AEs), with the most commonly reported AEs being fatigue, fever, and pain.ConclusionThe combination of HAIC with lenvatinib and immunotherapy yielded a high ORR, improved the conversion therapy rate, and prolonged both OS and PFS in patients with uHCC while maintaining a favorable safety profile. BCLC stage was identified as an independent prognostic factor influencing the success of conversion therapy, with patients in stage B deriving significant survival benefits post-conversion.